2012
DOI: 10.4028/www.scientific.net/amr.512-515.2500
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Coal Biodesulfurization by Mixed Culture Column Leaching

Abstract: The removal of sulfur in coal before its combustion can reduce its environmental pollution, and microbial desulfurization should have good application prospects. Some species of bacteria have been used in the process of coal desulfurization, and our previous study demonstrated that mixed culture should be more efficient than pure culture by shaking cultivation. In this study, column leaching was investigated, due to its similarity to the industrial heap leaching. The mixed culture consisted of three st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…And the total sulfur removal rate of 65.23% was obtained, in which the removal rate of organic sulfur was 81.45%, inorganic sulfur of 38.78%. Although pyritic desulfurization was worse than some of the reported results, 13 total desulfurization of the two-step approach was better than the majority of other leaching test results, 10,24,30 which demonstrated that two-step biodesulfurization could further expand in future. Compared with the total desulfurization rate of 67.83% of our previous flotation-biodesulfurization method, the "two-step" bioleaching method was slightly lower than it, 18 but it was a more energy-saving and economical technology.…”
Section: "Two-step" Leaching Biodesulfurization Testmentioning
confidence: 55%
See 2 more Smart Citations
“…And the total sulfur removal rate of 65.23% was obtained, in which the removal rate of organic sulfur was 81.45%, inorganic sulfur of 38.78%. Although pyritic desulfurization was worse than some of the reported results, 13 total desulfurization of the two-step approach was better than the majority of other leaching test results, 10,24,30 which demonstrated that two-step biodesulfurization could further expand in future. Compared with the total desulfurization rate of 67.83% of our previous flotation-biodesulfurization method, the "two-step" bioleaching method was slightly lower than it, 18 but it was a more energy-saving and economical technology.…”
Section: "Two-step" Leaching Biodesulfurization Testmentioning
confidence: 55%
“…After the test was finished, the coal samples were washed and dried, and the total sulfur content was measured by the Eschka method to calculate the desulfurization rate. The two forms of sulfur content in experimental coal, inorganic sulfur and organic sulfur, were determined according to the GB/T214‐2007 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of bacteria caused the etching of coal particles, which resulted in less mineral acid solution, which made the pH value of the system in the experimental group rise. However, the bacteria adsorbed on the coal particle surface could constantly metabolize pyrite sulfur effectively, and a large number of H + were generated, which caused a sustained drop in the pH of the desulfurization system …”
Section: Resultsmentioning
confidence: 99%
“…Of the total sulphur, 43% was pyritic sulphur [178]. Subsequent studies on column reactors were undertaken by Yang et al [179]. They employed a 50 cm-high column, having an inner diameter of 650 mm.…”
Section: Scale-up Initiatives For Coal Biodesulphurizationmentioning
confidence: 99%